GAMBARAN PENGHARGAAN FINANSIAL, KESELAMATAN & KESEHATAN KERJA SERTA KEPUASAN KERJA PADA PT. HALEYORA POWER BANJARAN KAB. BANDUNG - Fadllillah, Nida; Sumiyati, Sumiyati; Widjajanta, Bambang (Journal of Business Management Education (JBME), 2018)
Purpose - The purpose of this study is to see the description of financial reward, occupational health and safety and job satisfactionDesign/methodology/approachh - The design of this study was cross sectional. This research uses descriptive approach with explanatory survey method and total of 66 respondents. A questionnaire was used as a research instrument to collect data from respondents. Analytical technique used is descriptive technique by using frequency distribution.Findings - Based on the results of the research using descriptive analysis, the results obtained that the financial reward is in quite suitable category with a score of representative 70,8%, occupational health and safety is in the good category with a score of representative 79% and job satisfaction is in the high Â category with a score of representative 78,5%.Originality/value - This study provides a basic understanding issues of financial rewards, occupational safety health and job satisfaction. The difference with the previous research is the variable of appreciation which examined the disability only for financial reward, the object of research studied in service sector, theory and reference used the latest theories.